Numerical study of the heat transfer characteristics of Helium-Air flow in PCHE with zigzag channel - Haidong Liu; Qiao Zeng; Deqi Chen; Yi Xiao; Yangyang Wang; Mingxia Liu; Xiaoli Qu (Case Studies in Thermal Engineering)
The PCHE is a critical component in the intermediate heat exchanger of mobile micro-reactors. This study conducts a numerical investigation of the flow and heat transfer characteristics of helium-air within the zigzag channels of the PCHE under 69 different thermal-hydraulic operating conditions. The results reveal that the model validation shows good agreement, with maximum errors in the Nu and f of 10.75 % and 4.81 %, respectively. Changes in thermal-hydraulic parameters exert negligible effects on the inlet and outlet pressure drops for both helium and air (ΔPₕₑ ≈ 10 kPa, ΔPₐᵢᵣ ≈ 100 kPa). The helium-side inlet temperature and mass flow play a dominant role in determining the heat transfer characteristics of the PCHE. The Nu and h for variations in the helium-side inlet temperature are 19.66 % and 25.98 % higher, respectively, compared to the air-side. For variations in the inlet mass flow, the Nu and h are approximately 1.2 times greater on the helium-side than on the air-side. As both parameters increase, the overall heat transfer capacity of the PCHE is significantly enhanced. This study provides valuable theoretical insights for future experimental investigations and optimization designs of the flow and heat transfer characteristics of helium and air within the PCHE.